Hierarchical nature of hydrogen-based direct reduction of iron oxides. (May 2022) - Ma, Yan; Souza Filho, Isnaldi R.; Bai, Yang; Schenk, Johannes; Patisson, Fabrice; Beck, Arik; van Bokhoven, Jeroen A.; Willinger, Marc G.; Li, Kejiang; Xie, Degang; Ponge, Dirk; Zaefferer, Stefan; et al.
Abstract: Fossil-free ironmaking is indispensable for reducing massive anthropogenic CO2 emissions in the steel industry. Hydrogen-based direct reduction (HyDR) is among the most attractive solutions for green ironmaking, with high technology readiness. The underlying mechanisms governing this process are characterized by a complex interaction of several chemical (phase transformations), physical (transport), and mechanical (stresses) phenomena. Their interplay leads to rich microstructures, characterized by a hierarchy of defects ranging across several orders of magnitude in length, including vacancies, dislocations, internal interfaces, and free surfaces in the form of cracks and pores. These defects can all act as reaction, nucleation, and diffusion sites, shaping the overall reduction kinetics. A clear understanding of the roles and interactions of these dynamically-evolving nano-/microstructure features is missing. Gaining better insights into these effects could enable improved access to the microstructure-based design of more efficient HyDR methods, with potentially high impact on the urgently needed decarbonization in the steel industry.